Χρήση αιθέριων ελαίων φασκομηλιάς για τη διατήρηση καρπών τομάτας σε διαφορετικό στάδιο ωρίμανσης - Ρούσος, Χαράλαμπος (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, 2014)
Tomato fruits (Solanum lycopersicum L.) at breaker and red ripening stage were exposed to sage volatile oils (Salvia officinalis L.) at concentrations of 50 mg/L and 500 mg/L for 0, 2, 7, and 14 days and at temperature 12oC with the relevant humidity being 95%. The aim of the present study was first to investigate the effect of the different oil concentration in comparison with the exposure time and secondly the possibility of developing induction phenomenon when fruits were initially exposed to essential oils for 7 days and then were transferred to ambient temperature for another 7 days (memory effect-ME). According to the results of the current study, high concentrations of essential oil (500 mg/L) in red and breaker tomato fruits resulted in speeding up the metabolic process, resulting in higher respiratory activity and ethylene production. In red fruits, ethylene increased up to 22 and 6 times comparing with the relevant fruits stored in ambient air (control) for the period of 7 and 14 days, respectively. Likewise, in breaker fruits the increase of ethylene was observed being 11 and five times higher than control. Essential oil (50 mg/L and 500 mg/L) application decreased weight losses in breaker fruits up to 45% and 27% after 7 and 14 days respectively. In red fruits, the percentage of weight losses was observed being 30% and 38% after 14 days of essential oil application. Moreover, low concentrations of essential oil improved firmness in red fruits (in contrast with breaker tomatoes) with the best results being observed at the time period of 7 days. Essential oil application did not affect the concentration of total phenols in fruits, in contrast with lycopene and b-carotene. Vapour-treatment at high and low concentration did not affect the color and the content of total soluble solids and citric acid in both breaker and red tomatoes. Natural volatiles, including essential oils, may maintain fruit quality in addition to the well documented antimicrobial protection during fresh produce storage and retail.
Keywords: Solanum lycopersicum; Tomato Fruit; Sage Volatile Oil; Salvia Officinalis; Essential Oils; Καρπός Τομάτας; Αιθέρια Έλαια; Φασκομηλιά; Αιθέριο Έλαιο Φασκομηλιάς